Electroencephalographic Functional Connectivity With the Tacit Learning System Prosthetic Hand: A Case Series Using Motor Imagery - Iwatsuki, Katsuyuki; Hoshiyama, Minoru; Oyama, Shintaro; Yoneda, Hidemasa; Shimoda, Shingo; Hirata, Hitoshi (Frontiers in Synaptic Neuroscience, 2020)
We previously created a prosthetic hand with a tacit learning system (TLS) that automatically supports the control of forearm pronosupination. This myoelectric prosthetic hand enables sensory feedback and flexible motor output, which allows users to move efficiently with minimal burden. In this study, we investigated whether electroencephalography can be used to analyze the influence of the auxiliary function of the TLS on brain function. Three male participants who had sustained below elbow amputations and were myoelectric prosthesis users performed a series of physical movement trials with the TLS inactivated and activated. Trials were video recorded and a sequence of videos was prepared representing each individual’s own use while the system was inactivated and activated. In a subsequent motor imagery phase during which EEG signals were collected, each participant was asked to watch both videos of themself while actively imagining the physical movement depicted. Differences in mean cortical current and amplitude envelope correlation values between supplementary motor areas and each vertex were calculated. For all participants, there were differences in mean cortical current generated by the motor imagery tasks when the TLS inactivated and activated conditions were compared. The amplitude envelope correlation values were higher during the movement imagery task with TLS activation, although their distribution on the cortex varied between the three individuals. In both S1 and other brain areas, amplitude envelope correlation (AEC) values increased in conditions with the TLS activated. Evidence from this case series indicates that, in addition to motor control, TLS may change sensory stimulus recognition.